Genetic characterization of advanced conjunctival melanoma and response to systemic treatment. (May 2022) - Lodde, Georg C.; Jansen, Philipp; Möller, Inga; Sucker, Antje; Hassel, Jessica C.; Forschner, Andrea; Eckardt, Julia; Meier, Friedegund; Reinhardt, Lydia; Kähler, Katharina C.; Ziemer, Mirjana; Schlaak, Max; et al.
Abstract: Background: Conjunctival melanoma is a rare type of ocular melanoma, which is prone to local recurrence and metastasis and can lead to patient death. Novel therapeutic strategies have revolutionized cutaneous melanoma management. The efficacy of these therapies in conjunctival melanoma, however, has not been evaluated in larger patient cohorts. Methods: In this multi-center retrospective cohort study with additional screening of the ADOREG database, data were collected from 34 patients with metastatic conjunctival melanoma who received targeted therapy (TT) (BRAF ± MEK inhibitors) or immune checkpoint inhibitors (ICI) (anti-PD-1 ± anti-CTLA4). In 15 cases, tissue was available for targeted next-generation-sequencing (611 genes) and RNA sequencing. Driver mutations, tumor mutational burden, copy number variations and inflammatory/IFNγ gene expression signatures were determined. Results: Genetic characterization identified frequent BRAF (46.7%, 7/15), NRAS (26.7%, 4/15), NF1 (20%, 3/15), and TERT promoter (46.7%, 7/15) mutations. UV associated C>T and CC>TT mutations were common. Median follow-up time after start of first TT or ICI therapy was 13.2 months. In 26 patients receiving first-line ICI, estimated one-year progression-free survival (PFS) rate was 42.0%, PFS and overall survival (OS) 6.2 and 18.0 months, respectively. First-line TT was given to 8 patients, estimated one-year PFS rate was 54.7%, median PFS and OS 12.6 and 29.1 months, respectively. Conclusions: Our findings support the role of UV irradiation in conjunctival melanoma and the genetic similarity with cutaneous melanoma. Conjunctival melanoma patients with advanced disease benefit from both targeted therapies (BRAF ± MEK inhibitors) and immune checkpoint inhibitors. Highlights: Our findings support the role of UV irradiation in conjunctival melanoma. Oncogene mutation patterns are similar to cutaneous melanoma. In contrast to uveal melanoma, lymph node metastasis is common. Response to immune checkpoint inhibition (ICI) is better than in uveal melanoma. Targeted therapy (TT) should be considered in BRAF mutated conjunctival melanoma.